Developing Innovative Financing Scheme for Leveraging Energy Efficiency Deployment in Indonesia - Kurniawan, Robi; Kurniawan, Irwan Wahyu (Indonesian Journal of Energy, 2022)
Having great potential, a mechanism that can leverage private involvement in energy efficiency deployment should be developed in emerging markets such as Indonesia. This study aimed to formulate an implementable financial innovative scheme for leveraging energy efficiency deployment in the country. Scrutinizing relevant studies and interviewing relevant stakeholders such as the Ministry of Finance, Ministry of Energy and the Financial Institution, we formulated a blended financial scheme for an energy efficiency project. Main stakeholders will include the scheme, including fund facilitator, trustee, custodian bank and energy user/energy service company. In our proposed scheme, Indonesia Environment Fund (IEF) is obtained the fund from the fund facilitator. IEF will act as a trustee that delivers funds for the Custodian Bank. The bank will disburse the fund to the feasible energy efficiency project or through an energy service company. In this scheme, since banks get lower interest rate funds from the trustee, they will disburse the fund to the customer with a lower interest rate than a commercial rate. Consumers utilize the fund for their energy efficiency projects. Utilizing a proposed scheme to an energy efficiency project case study, it is found that the proposed scheme potentially reduces the interest rate and leverages the project viability in a certain condition. Doing the sensitivity analysis by comparing interest rate and IRR (Internal Rate of Return) in several loan periods, we found that the shorter period of the loan and lower interest rate can improve projects feasibility. For instance, simulating a 5-year loan, it is found that reducing the interest rate from 12% to 7% could improve up to 2% IRR of the project case. Therefore, the scheme can catalyze private-sector investments mobilization for energy efficiency deployment in the country. Furthermore, it can support the country's energy security enhancement.